Dynamic doping in planar ionic transition metal complex-based light-emitting electrochemical cells - Meier, Sebastian B.; Reenen, Stephan van; Lefevre, Bastien; Hartmann, David; Bolink, Henk J.; Winnacker, Albrecht; Sarfert, Wiebke; Kemerink, Martijn (Advanced functional materials, 2013)
Using a planar electrode geometry, the operational mechanism of iridium(III) ionic transition metal complex (iTMC)-based light-emitting electrochemical cells (LECs) is studied by a combination of fluorescence microscopy and scanning Kelvin probe microscopy (SKPM). Applying a bias to the LECs leads to the quenching of the photoluminescence (PL) in between the electrodes and to a sharp drop of the electrostatic potential in the middle of the device, far away from the contacts. The results shed light on the operational mechanism of iTMC-LECs and demonstrate that these devices work essentially the same as LECs based on conjugated polymers do, i.e., according to an electrochemical doping mechanism. Moreover, with proceeding operation time the potential drop shifts towards the cathode coincident with the onset of light emission. During prolonged operation the emission zone and the potential drop both migrate towards the anode. This event is accompanied by a continuous quenching of the PL in two distinct regions separated by the emission line.
Gesehen am 05.12.2019